Wing-external store aerodynamic interferences of a subsonic aircraft - Huong, Yu Saint (2001)
Modem fighter aircraft are mostly designed to carry its store externally. Installing store to an aircraft wing externally would have much engineering implication especially through the change in the aerodynamic characteristic. This research was carried out to study the application of the Computational Fluid Dynamics (CFD) method along with experimental methods in predicting the aerodynamic interference caused by these installations. Commercial CFD code. Fluent 5.3 had been validated using experimental results reported in the literature lor two dimensional, subsonic and transonic flow over the NACA 0012 and the RAE 2822 airfoil. Subsequently, low speed wind tunnel experiments were carried out over a wing model installed with an external store. The wing model was fabricated based on a digitized BAe Hawk 208 fighter wing. For further CFD code validation, the wind tunnel configurations were again simulated using the CFD method and its results were validated with the experimental results. Finally, a simplified full scale Hawk 208 aircraft model carrying an external store was simulated at various attitudes and flow speeds. In the two-dimensional subsonic flow, pressure distribution predicted by CFD was in good agreement and comparable to the experimental results. For the transonic two-dimensional flow validation, pressure distribution predicted by various flow models were slightly different from the experimental results (9% to -22.2% in term of CL). For wind tunnel configuration, an average of about 12% deviation in pressure distribution between the results predicted by the CFD method and measured in the wind tunnel. The results of the fu!! scale Hawk 208 simulation show that the aerodynamic interference caused by the store installation were mostly evidence on the lower wing surface and negligible on the upper surface at low angle of attack. This trend was reversed as the angle of attack was increased. The area of influence on the wing surface by store interference increased in line with the increased in airspeed.